A glimpse of the ERS International Congress 2022. Issue 2 (12th July 2022) - Gompelmann, Daniela; Farr, Amy; Simonds, Anita; Brightling, Christopher; Roche, Nicolas; Laveneziana, Pierantonio; Costello, Richard W.; Meiners, Silke; Troosters, Thierry; Cruz, Joana
The European Respiratory Society (ERS) International Congress is an annual event where thousands of experts from around the world come together to present and discuss the latest scientific and clinical advances in the respiratory field. During the pandemic, there was a need to change the format of the Congress from in-person to an online format (2020 and 2021) to limit the exposure to the coronavirus. This year, for the first time, the ERS Congress will take place in a hybrid format, i.e. in Barcelona (Spain) and online, from 4–6 September 2022. In this article, we provide an overview on what to expect from the ERS Congress 2022, including the "top picks" of the 2022 Congress programme from the leaders of the International Congress Programme Committee and a summary of the Early Career Member (ECM) session, which this year will address the "Steps for a successful career in respiratory research". An overview of what to expect from the European Respiratory Society (ERS) International Congress 2022, including the top picks of the International Congress Programme Committee and a summary of the Early Career Member session. https://bit.ly/3tNTlgY